2016
DOI: 10.1093/brain/aww099
|View full text |Cite
|
Sign up to set email alerts
|

Migraine with aura and risk of silent brain infarcts and white matter hyperintensities: an MRI study

Abstract: Migraine with aura is considered a putative risk factor for silent brain infarcts and white matter hyperintensities in women. In an MRI study of Danish female twins aged 30–60 years, Gaist et al. compare 172 affected women with 139 controls, but find no evidence to support the proposed associations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
50
3
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 23 publications
7
50
3
3
Order By: Relevance
“…The studies demonstrated that topical cortical application of ET‐1 potently elicits CSD‐like changes in cortical activity. Subsequent studies showed that the cause of CSD elicitation is most likely vasoconstrictive ischemia leading to areas of micronecrosis and not a direct neuronal effect of ET‐1 . This is in line with the general observation that CSD can be induced by various forms of cortical damage, including cortical infarction .…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The studies demonstrated that topical cortical application of ET‐1 potently elicits CSD‐like changes in cortical activity. Subsequent studies showed that the cause of CSD elicitation is most likely vasoconstrictive ischemia leading to areas of micronecrosis and not a direct neuronal effect of ET‐1 . This is in line with the general observation that CSD can be induced by various forms of cortical damage, including cortical infarction .…”
Section: Discussionsupporting
confidence: 67%
“…The likely reason for this is that circulating ET‐1 would have to cross the blood‐brain barrier (BBB) to exert the effects observed in the animals, and ET‐1 passage through the BBB is very limited . In addition, spontaneous aura attacks are not induced by this mechanism since migraine attacks with aura are not generally associated with the vascular cerebral damage …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, despite some of the limitations, our findings are more comprehensive and clinically relevant. Furthermore, our finding is in line with the recent report that MA is not associated with silent stroke on MRI (average age 48) in a well‐designed MRI image study . Additionally, risk of ischemic stroke was not higher in migraineurs (MA and MO) after adjusting for a comprehensive lists of cardiovascular risk factors in a large population‐based Swedish twin study (mean age at the time of enrollment 45.3) .…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, researchers have argued that it is the deep white matter lesions on MRI and not SBIs that produces the dizziness and headache of non-specific cause (13,14) . Further, Gaist et al, in a recent study, have reported the lack of evidence of an association between the white matter hyperintensities, SBIs, and migraine with aura (5) .…”
Section: Discussionmentioning
confidence: 96%
“…Despite being asymptomatic, the occurrence of SBIs have been associated with the development of certain nonspecific neurological symptoms such as dizziness, forgetfulness, age, and hypertension, as reported by Hougaku et al (4) . Even though several studies have been conducted on association of migraine and SBI (5) , there is lacuna in studies exploring the association of other non-specific neurological symptoms in patients diagnosed with SBI. Therefore, this study examines the patients with non-specific neurological symptoms for the presence of SBIs and is believed to be the first Indian study to assess the role of these symptoms in diagnosing SBIs.…”
Section: Introductionmentioning
confidence: 99%